Use of plant extracts as an efficient alternative therapy of respiratory tract infections - Šmejkal, Karel; Rjašková, Veronika (Ceska a Slovenska farmacie, 2016)
Medicinal plants are advantageously used in the treatment of respiratory tract diseases. Upper respiratory tract catarrh is one of the diseases associated with seasonal weakening of immunity, and therefore, plant drugs with a non-specific immunomodulation effect are often used. Such plants include, but are not limited to, Echinacea (Echinacea purpurea) and American ginseng (Panax quinquefolius). In combination with medicinal plants having antibacterial and antiseptic effects, such as thyme (Thymus vulgaris) and pelargonium (Pelargonium sidoides), they can constitute efficient help in the treatment of respiratory tract diseases, shorten the duration of the disease and reduce the need of antibiotic therapy. The text presented summarizes the basic information about these plants, their ingredients, mechanisms of action and clinical tests confirming their effect and monitoring eventual adverse effects.Key words: Echinacea purpurea Panax quinquefolius Pelargonium sidoides Thymus vulgaris upper respiratory tract catarrh immunity.
Keywords: fytoterapie; Pelargonium; Plant Extracts; Humans; infekce dýchací soustavy; rostlinné extrakty; Thymus (rostlina); Respiratory Tract Infections; Thymus Plant; lidé; Phytotherapy